The Emancipation Proclamation - Lincoln, Abraham, 1809-1865 (Salt Lake City, UT : Project Gutenberg, 2007)
"The Emancipation Proclamation" by Abraham Lincoln is a presidential proclamation issued on January 1, 1863, during the American Civil War. This executive order changed the legal status of more than 3.5 million enslaved African Americans in Confederate states from enslaved to free. The Proclamation transformed the Civil War from a struggle to preserve the Union into a fight to end slavery, energizing abolitionists while outraging Southern sympathizers and reshaping the nation's future. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Emancipation_Proclamation
Release date is 2007-07-16
Keywords: United States. President (1861-1865 : Lincoln). Emancipation Proclamation